PENGARUH BERMAIN GAME ONLINE MOBILE LEGENDS TERHADAP KOMUNIKASI KEKERASAN VERBAL PADA REMAJA DESA TANGKIT BARU, KECAMATAN SUNGAI GELAM, KABUPATEN MUARO JAMBI, PROVINSI JAMBI - Andi Zutrian Fahri, (2022)
This study aims to determine the effect of playing the online game Mobile Legends on verbal violence communication in adolescents using the S-O-R theory (Stimulus, Orginism, Response). The method used is quantitative explanatory by using primary data sources in the form of a questionnaire as a research instrument. The population in this study were teenagers in Tangkit Baru Village, Sungai Gelam District, Muaro Jambi Regency, Jambi Province. The sampling technique was carried out using a non-probability sampling technique with a saturated sampling method or a census because the population was small, namely 40 teenagers. Data analysis was carried out by researchers with validity test, reliability test, correlation test, simple linear regression test, coefficient of determination test, and hypothesis testing. The results showed that there was a relationship between playing the online game Mobile Legends with verbal violence communication in adolescents, including in the fairly strong category, namely 0.540. The coefficient of determination shows the effect of playing the online game Mobile Legends on verbal violence communication in adolescents by 18.5% while the rest is influenced by other factors not examined in this study. This result is reinforced by the results of hypothesis testing with a t-count value of 2.942 > ttable which is 2.024 with a significance value of 0.006 <0.05. This shows that H0 is rejected and Ha is accepted, which means that there is an influence between playing the online game Mobile Legends on violent communication among teenagers.